Development mutants of Streptomyces coeruleorubidus, a producer of anthracyclines: isolation and preliminary characterization - Blumauerová, M; Pokorný, V; Stastná, J; Hostálek, Z; Vanĕk, Z (Folia microbiologica, 1978)
The wild strain Streptomyces coeruleorubidus JA 10092 was found to segregate into two spontaneous morphological variants (spo-1 and bld-1) with a different ability to form aerial mycelium in media with glucose as the main carbon source. Six new types of developmental mutants were obtained from the bald variant bld-1 after treatment with mutagens (UV light, gamma radiation, nitrous acid) and after natural selection. Formation of the aerial mycelium was fully suppressed in the bld-2 type growing on media both with glucose and with starch. The other types were bald only on starch media, forming the aerial mycelium on media with glucose; types spo-2, spo-3, spo-4 and spo-5 differed in size, shape and surface structure of spores, the type whi formed asporogenous aerial hyphae.
Keywords: mutace; Aminoglycosides; selekce (genetika); Selection, Genetic; Spores, Bacterial; Starch; Mutation; spory bakteriální; glukosa; škrob; Glucose; aminoglykosidy; Streptomyces